2021
DOI: 10.1186/s13063-021-05673-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect evaluation of Individual Placement and Support (IPS) for patients with substance use disorders: study protocol for a randomized controlled trial of IPS versus enhanced self-help

Abstract: Background Employment is associated with better outcomes of substance use treatment and protects against relapse after treatment completion. Unemployment rates are high for people with substance use disorders (SUD) who undergo treatment, with Norwegian estimates ranging from 81 to 91%. Evidence-based vocational models are lacking for patients in SUD treatment but exist for patients with psychosis in terms of Individual Placement and Support (IPS). The aim of the IPS for substance use disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…A Norwegian five-year prospective study of drug users found that 45% were imprisoned at least once during the study period, with a mean duration of 65 incarcerated days ( Gjersing & Bretteville-Jensen, 2021 ). We know that treatment, including opioid maintenance treatment for persons with opioid dependency, is associated with reductions in criminal behaviour and convictions ( Gossop et al, 2005 ; Lind et al, 2005 ; Soyka et al, 2012 ). The average cost per inmate per day in Norway is €318 ( Aebi & Tiago, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Norwegian five-year prospective study of drug users found that 45% were imprisoned at least once during the study period, with a mean duration of 65 incarcerated days ( Gjersing & Bretteville-Jensen, 2021 ). We know that treatment, including opioid maintenance treatment for persons with opioid dependency, is associated with reductions in criminal behaviour and convictions ( Gossop et al, 2005 ; Lind et al, 2005 ; Soyka et al, 2012 ). The average cost per inmate per day in Norway is €318 ( Aebi & Tiago, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of employment on substance use, mental health and quality of life is of utmost importance for those involved. These outcomes will be made available through our ongoing RCT (Rognli et al, 2021).…”
Section: Characterising Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is reasonable to assume that more intensive support is required for a cohort characterised by mental health problems, a history of trauma and the stigma of criminalisation. The review notes that a randomised control trial is underway for Individual Placement and Support (IPS) for the substance misuse population in England (Rognli et al, 2021). A recent systematic review of the IPS initiative found that such programmes improve employment rates, hours worked and wages earned for people with drug and alcohol problems (Harrison et al, 2020).…”
Section: The Black Reviewmentioning
confidence: 99%
“…Det er imidlertid ikke knyttet forskning til noen av disse tiltakene, og det finnes ingen rapporter eller evalueringer om IPS og rus. En pågående RCT ved Oslo universitetssykehus avsluttet inklusjon av deltakere i juni 2022, og vil vaere et viktig bidrag til den internasjonale litteraturen om IPS og rus (Rognli et al, 2021).…”
Section: Evidensgrunnlag For Ips Ved Ruslidelseunclassified